(untitled) (The International Journal for Scientific Research, 2026)
Abstract: This study aimed to shed light on some issues addressed by Islamic teachings that have been misinterpreted by non-Muslims. The researcher employed a descriptive-analytical approach. This research clarifies these issues and concludes that negative media portrayals have presented a distorted image of Islam, thus necessitating clarification of the facts. Among the recommendations is the importance of explaining the Islamic perspective on these issues under discussion. Muslim scholars are urged to undertake this challenging task in this era of modernity, globalization, and Westernization.